2020
DOI: 10.1167/tvst.9.8.2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Fundus Autofluorescence: Advanced Analysis Tools

Abstract: To use multimodal retinal images (including quantitative fundus autofluorescence [QAF]) for spectral-domain optical coherence tomography (SD-OCT)-based image registration and alignment. For each age decade of healthy adults, normative fine-grained QAF retinal maps are generated and advanced methods for QAF image analysis are applied. Methods: Multimodal retinal images were obtained from 103 healthy subjects (age 19-77 years; unremarkable retina/macula, age-appropriate clear optic media). Custom written FIJI pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…Furthermore, well-trained technical assistance is required to guarantee reliability and repeatability of QAF imaging. Previous studies in our cohorts showed mean variability of about 8% in normal subjects 37 and <12% in patients with maculopathy, comparable to results from other groups. 31 In conclusion, this study is a prospective preclinical report on increased quantitative short wavelength FAF during CQ/HCQ treatment, compared to QAF of healthy controls.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, well-trained technical assistance is required to guarantee reliability and repeatability of QAF imaging. Previous studies in our cohorts showed mean variability of about 8% in normal subjects 37 and <12% in patients with maculopathy, comparable to results from other groups. 31 In conclusion, this study is a prospective preclinical report on increased quantitative short wavelength FAF during CQ/HCQ treatment, compared to QAF of healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, well-trained technical assistance is required to guarantee reliability and repeatability of QAF imaging. Previous studies in our cohorts showed mean variability of about 8% in normal subjects 37 and <12% in patients with maculopathy, comparable to results from other groups. 31 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations